Genetic Variation and Anticancer Activity of Ndrographis Paniculata Germplasm from Malaysia - Abdalla, Jebril Ali (2005)
Andrographis paniculata (Acanthaceae) is a medicinal herb endowed with curative properties against a variety of ailments including cold, fever, liver diseases, diabetes and cancer. Pharmacological studies have demonstrated that the major compound of the plant, diterpene lactone andrographolide, have in vitro antitumour activity against human breast cancer cell lines MCF- 7. Twenty-six A. paniculata accessions were collected from three states in Peninsula Malaysia (Selangor, Negeri Sembilan and Perak) to study the genetic variations, phytochemical variations and cytotoxicity activity against MCF-7 cells, in order to identify promising accessions. Genetic variations of 26 A. paniculata were investigated using inter simple sequence repeat (ISSR) analysis. Of the 28 primers screened, 17 produced highly reproducible ISSR bands. Using these primers, 123 discernible DNA fragments were generated with 35 (29 %) being polymorphic, indicating low levels of polymorphism at the populations level. At the 0.84 Jaccard's similarity the A. paniculata accessions were divided into 7 distinct groups, the genetic clustering was in agreement with the geographical locations 1 distances. Dry material of A. paniculata was extracted in petroleum ether dichloromethane, methanol, and mixture of dichloromethane/methanol (1:l) for bioactivity testing. The results indicate that the dichloromethane extracts retains the active compounds contributing for the anticancer activity. Dichloromethane extracts significantly inhibits the proliferation of MCF-7 breast cancer cell lines at low concentrations (1 1 .Opg/ml). Analysis of the contents of active components of A. paniculata, namely andrographolide (ANDRO), neoandrographolide (NAG) and 14-deoxy-I 1, 12- didehydroandrographolide (DDAG), was carried out using high performance liquid chromatography. Accession 11 179s was most superior in terms of andrographolide content, whereby it had 1% in dry weight. Moreover, accessions 1 l269P, 1 l265P, 1 1261 P and 1 l284P also showed higher content of ANDRO of 0.84, 0.78, 0.76 and 0.70% respectively in dry weight. ~ERWSTM(AANw TAN ABOUL SAMAD WJ~VERSTI WTRA W-AySA The lowest amounts for the 3 active compounds were found in accession 1 1 169S, with value of 0.1 1 - 0.25%. Dichloromethane (DCM) extracts of the 26 accessions were tested for cytotoxic effect on human breast cancer cell lines, MCF-7, using a microculture tetrazolium (MTT) assay. The accessions had similar cytotoxic activity, determined by the 50% inhibitory concentrations (ICfio). Accession 11276P had the lowest IC50value of 2.2 pglml, and the highest lCBovalue of 6.6 pglml was shown by accession 11212NS. - - In correlation study, the ICso values were negatively correlated with ANDRO (PI 0.05) and NAG (PI 0.01), which indicates the choice of accessions with high contents of ANDRO and NAG, results in good activity against MCF-7 human breast cancer cell lines. Also heritability for phytochemicals ANDRO, NAG and DDAG in the present study confirms that these compounds are mainly under genetic control in A. paniculata germplasm. Accessions 1 1 1 79S1 1 1 269P, 11 265P, 11 261 P and 1 1284P are considered to be the most valuable accessions with high potential for anticancer.